PERTUMBUHAN GULMA DAN HASIL KACANG TANAH PADA BERBAGAI KERAPATAN TANAM - Hidayati. Mas’ud (Universitas Tadulako, 2013)
This research was conducted in the Sub District of Sigi Biromaru Loru District Donggala. The research used a randomized completely block design (CBD) with 7 kinds of planting spaces included J1 = (15 x 15) cm2, J2 = (15x 20) cm2, J3 = (20 x 20) cm2, J4 = (20 x 25) cm2, J5 = (25 x 25) cm2, J6 = (25 x 30) cm2, and J7 = (30 x 30) cm2. Each experimental unit was repeated 4 times, so that there were 28 units. Observation was done on the Some Dominance Ratio (SDR) of weeds, number of pods containingseeds plant-1,podweightcontaining seeds plant-1, weightof pods ha-1, weight of 100 seed grainsand dried beans yield. Data were analyzedusinganalysis of variance. Ifthe effect was significant then the test was continued using Honest Significance Difference at 5% level. Largest SDR was found in nut grass group (46.92%, Cyperus rotundus) followed by broadleaf grass group (24.62%, Trianthema portulacstrum), and barnyard grass group (15.84%, Echinocloa crussgalli). Various planting spaceshad significant effect on peanut yield components ie. number of pods containing seeds plant-1, weight of pods containing seeds plant-1 and pod weight ha-1. The planting space of 20 cm x 25 cm increased peanut yield. Key Words : Crop density,peanut yield, and weeds growth.